2017
DOI: 10.18203/2349-2902.isj20171626
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of serum hyperbilirubinemia in acute appendicitis and its complications

Abstract: Background: To increase diagnostic accuracy and to decrease complication rates secondary to acute appendicitis, a variety of different approaches have been described, including predictive scoring systems. To prevent the catastrophic effects of perforated appendix, a surgeon needs diagnostic tools which may signal perforation of appendix at earliest, as a result of which the delay in the management of perforated appendix will not be witnessed. Keeping in view the above facts, the diagnostic value of serum bilir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Hence it can be noted that hyperbilirubinemia was associated with most of appendiceal perforation cases. 7,13,14,18 Appendiceal perforation cases had higher levels of bilirubin compared to acute appendicitis cases. So, it can be stated that patients with features suggestive of acute appendicitis with higher values of serum bilirubin are more vulnerable to appendiceal perforation than those with normal to slightly elevated total serum bilirubin.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Hence it can be noted that hyperbilirubinemia was associated with most of appendiceal perforation cases. 7,13,14,18 Appendiceal perforation cases had higher levels of bilirubin compared to acute appendicitis cases. So, it can be stated that patients with features suggestive of acute appendicitis with higher values of serum bilirubin are more vulnerable to appendiceal perforation than those with normal to slightly elevated total serum bilirubin.…”
Section: Discussionmentioning
confidence: 95%
“…6 Thus to prevent the catastrophic effects of perforated appendix, a surgeon might need a diagnostic aid which can signal perforation at its earliest. 7 Hyperbilirubinemia is recently postulated as laboratory marker for diagnosing acute appendicitis and determining its severity. 8 Studies have shown that bacterial infection causes disruption in production and excretion of bile.…”
Section: Introductionmentioning
confidence: 99%